2017
DOI: 10.1038/s41598-017-13243-0
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte calcium waves propagate proximally by gap junction and distally by extracellular diffusion of ATP released from volume-regulated anion channels

Abstract: Wave-like propagation of [Ca2+]i increases is a remarkable intercellular communication characteristic in astrocyte networks, intercalating neural circuits and vasculature. Mechanically-induced [Ca2+]i increases and their subsequent propagation to neighboring astrocytes in culture is a classical model of astrocyte calcium wave and is known to be mediated by gap junction and extracellular ATP, but the role of each pathway remains unclear. Pharmacologic analysis of time-dependent distribution of [Ca2+]i revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 58 publications
2
82
0
2
Order By: Relevance
“…Alternatively, we have reported that elevated Ca ++ increases gap junction connectivity between corneal epithelial cells 29 . In astrocytes, mechanically-induced Ca ++ ion increases and their subsequent propagation to neighboring cells were found to have two distinct patterns: (1) persistent increases were found to propagate rapidly via gap junctions in the www.nature.com/scientificreports www.nature.com/scientificreports/ proximal region, and (2) transient increases were found to propagate slowly via extracellular ATP in the distal region 11 . It has also been reported that forced expression of gap junction connexins successfully enables gap junction-deficient cell lines to propagate intercellular Ca ++ waves, stimulating secretion of ATP 5-to 15-fold from the cells 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, we have reported that elevated Ca ++ increases gap junction connectivity between corneal epithelial cells 29 . In astrocytes, mechanically-induced Ca ++ ion increases and their subsequent propagation to neighboring cells were found to have two distinct patterns: (1) persistent increases were found to propagate rapidly via gap junctions in the www.nature.com/scientificreports www.nature.com/scientificreports/ proximal region, and (2) transient increases were found to propagate slowly via extracellular ATP in the distal region 11 . It has also been reported that forced expression of gap junction connexins successfully enables gap junction-deficient cell lines to propagate intercellular Ca ++ waves, stimulating secretion of ATP 5-to 15-fold from the cells 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Gap junctions and ATP have both been shown to promote intercellular calcium wave propagation 11 . Gap junctions are specialized plasma membrane structures that provide a communication pathway among adjacent cells, facilitating direct exchange of small molecules (<1000 Da) including ions, metabolites and second messengers (e.g., calcium, glucose, cAMP, cGMP, IP3) 12 .…”
mentioning
confidence: 99%
“…ATP is also important in the propagation of Ca 2+ waves through astrocyte networks (Fujii, Maekawa, & Morita, 2017). Moreover, vasoactive substance release is regulated by astrocytic Ca 2+ waves and ATP-induced Ca 2+ release from intracellular stores within astrocytes (Metea & Newman, 2006).…”
Section: Piezo1 and Atp-responsiveness In Astrocytesmentioning
confidence: 99%
“…The role of gap-junctions in K + spatial buffering has been suggested (Kofuji and Newman, 2004;Ma et al, 2016). Ca 2+ events propagate in the astrocytic network through two major mechanisms -extracellular, involving neurotransmitter release, and intracellular, through the gap-junctions (Fujii et al, 2017;Semyanov, 2019). Gap-junction coupling has two possibilities for plasticity: (1) change in the number of connections and…”
Section: Discussionmentioning
confidence: 99%
“…3f). Such changes in Ca 2+ activity arguably reflect cell uncoupling in the astrocytic network and the inability of Ca 2+ events to propagate through the gap-junctions to the neighboring cells (Fujii et al, 2017). The integral of astrocytic Ca 2+ activity was unchanged in CR (p = 0.27, Mann-Whitney test with control, Fig.…”
Section: Cr Modifies Spatiotemporal Properties Of Spontaneous Ca 2+ Ementioning
confidence: 93%